2015
DOI: 10.1371/journal.pone.0140120
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Side Chain at Position 296 of Antibody Fc in Interactions with FcγRIIIa and Other Fcγ Receptors

Abstract: Antibody-dependent cellular cytotoxicity (ADCC) is an important effector function determining the clinical efficacy of therapeutic antibodies. Core fucose removal from N-glycans on the Fc portion of immunoglobulin G (IgG) improves the binding affinity for Fcγ receptor IIIa (FcγRIIIa) and dramatically enhances ADCC. Our previous structural analyses revealed that Tyr–296 of IgG1-Fc plays a critical role in the interaction with FcγRIIIa, particularly in the enhanced FcγRIIIa binding of nonfucosylated IgG1. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
0
16
1
Order By: Relevance
“…1b ). This is also in marked contrast to the observation of the same sFcγRIIIa in complex with the nonfucosylated Fc glycoform, in which the Asn162 glycan is extensively involved in interactions with the Fc glycan 13 15 . Because the sFcγRIIIa glycoprotein used in the crystallization had a homogeneous glycoform exclusively exhibiting the bi-antennary complex-type oligosaccharide Gal 2 GlcNAc 2 Man 3 GlcNAc 2 (Fuc), the ambiguous electron density of the Asn162 glycan of sFcγRIIIa indicates its conformational disorder, presumably because the intermolecular carbohydrate-carbohydrate interaction was weakened in the presence of the core fucose residue of the Fc glycan 4 , 6 12 .…”
Section: Resultscontrasting
confidence: 88%
See 3 more Smart Citations
“…1b ). This is also in marked contrast to the observation of the same sFcγRIIIa in complex with the nonfucosylated Fc glycoform, in which the Asn162 glycan is extensively involved in interactions with the Fc glycan 13 15 . Because the sFcγRIIIa glycoprotein used in the crystallization had a homogeneous glycoform exclusively exhibiting the bi-antennary complex-type oligosaccharide Gal 2 GlcNAc 2 Man 3 GlcNAc 2 (Fuc), the ambiguous electron density of the Asn162 glycan of sFcγRIIIa indicates its conformational disorder, presumably because the intermolecular carbohydrate-carbohydrate interaction was weakened in the presence of the core fucose residue of the Fc glycan 4 , 6 12 .…”
Section: Resultscontrasting
confidence: 88%
“…In the non-fucosylated system, this innermost residue of the Fc chain A glycan is in close proximity to the innermost part, i.e., GlcNAc1 and GlcNAc2, of the Asn162 glycan. The previous crystallographic data indicated that the Asn162 glycan of sFcγRIIIa is involved in intermolecular interactions with the IgG1-Fc glycan in its nonfucosylated form 13 15 . The crystal structure, in which the core and the Man α1-3 arm of the Asn162 glycan of sFcγRIIIa are in contact with the Fc glycan, corresponds in terms of these distances to the most highly populated state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anti‐DNP antibody‐binding affinity for recombinant hFcγRIIIa (hFcγRIIIa‐158V, hFcγRIIIa‐158F) and hFcRn (pH 6.0 and pH 7.4) was tested with Biacore (GE Healthcare), as previously described, using human anti‐IgG2 isotype control antibody …”
Section: Methodsmentioning
confidence: 99%